Représentation et théorie : une analyse critique du point de vue constructiviste - Alain Firode (Nantes Université, 2013)
Many contemporary science didacticians claim that a successfull learning is a long-term change in mental representations. This paper aims at showing, by using some analysis taken from the popperian epistemology, that this point of view involves a confusion. A confusion between, on the one hand, the psychological effects which can result from the learning of a scientific knowledge and, on the other hand, the intellectual activity by which this learning takes place. According to Popper, the process by which we succeed in knowing an intellectual object, such as a scientific theory, is not essentially different from the process by which we learn to know a physical object. It consists of « operating with world three objects » and not of changing our « mental representations ».